Coordinated optimisation of multi-level rail transit network and Regional spatial: International contextual differences and the case of Shanghai - Ma, Yuxiao; Zhang, Qiao; Deng, Jing; Huang, Jianzhong (AESOP, 2024)
As the urbanisation rate in China continues to rise, there is an urgent need to enhance the rail transit system to facilitate the growth of major cities and regions. This study examines the contrasts and interconnections between China's rail transit system concepts and those of other countries, as well as the discrepancies in the histories of construction and operational approaches. Based on a clear understanding of these differences, the study employs multiple data sources to analyse the rail transit network in Shanghai. It finds that the network is well-developed, particularly in high-speed railways and metros. However, it lacks an intermediate level. To address this issue, the study proposes a multi-level rail transit network and spatially coordinated optimisation strategy tailored to urban demands. This strategy encompasses rail transit networks at three spatial scales, with specific strategies determined by the availability of urban resources. In conclusion, the study proposes a multi-level rail transit network and spatially coordinated optimisation strategy tailored to urban demands. This strategy encompasses rail transit networks at three spatial scales, with specific strategies determined by urban resources. The study emphasises the significance of recognising contextual variations and tailoring solutions to local requirements. Keywords: Regional integration; Rail transit network; Metropolitan areas; Cross-cultural comparison; Shanghai
Game changer? Planning for just and sustainable urban regions, Paris, 8-12th July 2024